Pengaruh Brand Image Dan Kualitas Produk Terhadap Keputusan Pembelian Air Minum Dalam Kemasan Merek Le Mineral Pada Mahasiswa Prodi Manajemen Universitas Medan Area - Arrazia, Zia; Aramita, Finta; Lestari, Indawati (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the influence of brand image and product quality on the purchasing decisions of bottled water brand Le Mineral among students in the Management Program at the University of Medan Area. The research approach used is quantitative, which will determine the extent of the influence of independent variables on dependent variables. The population in this study consists of 540 students from the Management Program at the University of Medan Area, selected from the 2022-2024 academic records (PDDikti 2025). The sampling technique used the Solvin formula, resulting in 84 respondents. Data analysis was conducted using SPSS 27 with multiple linear regression analysis to determine the influence of independent variables on dependent variables. The results of the study indicate that Brand Image has a positive and significant effect on Purchase Decisions. This is evident from the significant value (0.000) < 0.05. Product Quality has a positive and significant effect on Purchase Decisions, as evidenced by the significant value (0.000) < 0.05. Brand Image (X1) and Product Quality (X2) significantly influence Purchase Decisions, with the magnitude of influence of Brand Image (X1) and Product Quality (X2) accounting for 89.6% of Purchase Decisions of bottled water brand Le Mineral among students in the Management Program at the University of Medan Area.